2006
DOI: 10.1038/sj.bjc.6603450
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in Shenyang City, People's Republic of China: a population-based study

Abstract: To investigate the prevalence of, and risk factors for, cervical infection with human papillomavirus (HPV) in Shenyang City, People's Republic of China, we interviewed and obtained cervical cell samples from 685 women aged 15 -59 years enumerated from local population lists. Human papillomavirus DNA was detected in cervical cell samples using a GP5 þ /6 þ -based PCR assay for 44 HPV types. Human papillomavirus prevalence was 16.8% overall and 13.6% among women without cervical abnormalities (16.6% and 12.4%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
78
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 21 publications
24
78
8
Order By: Relevance
“…HPV52 and 58, however, were not as predominant as in similar surveys in China [16][17][18]. We also confirmed that the type distribution Major strengths of our present study include a large and population-based sample, the use of a standardized and well-validated HPV test allowing comparisons with similar studies around the world [9] and the presence of a concurrent series of women with ICC drawn from the same study area.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…HPV52 and 58, however, were not as predominant as in similar surveys in China [16][17][18]. We also confirmed that the type distribution Major strengths of our present study include a large and population-based sample, the use of a standardized and well-validated HPV test allowing comparisons with similar studies around the world [9] and the presence of a concurrent series of women with ICC drawn from the same study area.…”
Section: Discussionsupporting
confidence: 83%
“…The agespecific curve of HPV prevalence in Nepal resembled the flat age curves reported previously in some low-resource countries in Asia and Africa [15][16][17][18]24], albeit at a lower level of HPV prevalence. It clearly differed, on the other hand, from the steep decrease in HPV prevalence seen by age in high-and medium-resource countries in Europe, the Americas, and Asia [23,25].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations